A Comparative Study of Caffeine Levels in Coffee and Cocoa in Kenyan Supermarkets and Shops - Alex Muthengi; Silas Njiru; Juster Mungiria (Adventist University of Africa, 2024)
Background: Caffeine is an alkaloid belonging to the methylxanthine family. An overdose of caffeine causes the following side effects: restlessness, nervousness, excitement, insomnia, flushed face, diuresis, gastrointestinal disturbances, muscle twitching, rambling flow of thought and speech, and tachycardia or cardiac arrhythmia. This study aimed to determine the caffeine levels of various brands of coffee and cocoa and enlighten people on the safe and healthy consumption of the two products. Methods: Different brands of coffee and cocoa products were randomly sampled and purchased from supermarkets and shops in Nairobi, Kenya. Five samples of coffee and four brands of cocoa were purchased from a supermarket and taken to the laboratory for analysis. Caffeine was extracted, and quantitative analysis was done using High Performance Liquid Chromatography (HPLC). Results: The study found that coffee has a higher concentration of caffeine than cocoa. Coffee Brand A recorded the lowest level of caffeine with 30.9845 μ g/g, while Coffee Brand C recorded the highest level of caffeine with 426.9639 μ g/g. Among the Cocoa brands, Cocoa Brand B recorded the lowest level of caffeine (2.6367 μg/g), while Cocoa Brand C recorded the highest level of caffeine at 19.03 μ g/g. Conclusion: Therefore, there is a need to reduce coffee consumption per day because caffeine overdose can cause high blood pressure and other illnesses. Cocoa is recommended for consumption since it contains less caffeine per serving.